2020
DOI: 10.1097/md.0000000000023136
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Yanghe decoction regimen improves outcomes for idiopathic granulomatous mastitis

Abstract: The etiology of idiopathic granulomatous mastitis (IGM), a rare inflammatory breast disease, is not understood. There is no consensus regarding the treatment of IGM. The purpose of this study was to determine the efficacy of surgery combined with traditional Chinese medicine for the treatment of IGM. We retrospectively analyzed 53 patients of IGM who were treated with surgical excision at our hospital. Group A (n = 25) included patients treated with only surgery, and Group B included patients treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Most patients had a good outcome after treatment. There is also recent clinical research suggesting that traditional Chinese medicine is effective in treating mastitis, indicating the potential advantage of traditional Chinese medicine ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most patients had a good outcome after treatment. There is also recent clinical research suggesting that traditional Chinese medicine is effective in treating mastitis, indicating the potential advantage of traditional Chinese medicine ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…[17] Combined with surgery, it can significantly shorten the treatment period and improve the surgical cure rate. [18] Overall, TCM has the effect of increasing the cure rate and decreasing the recurrence rate without obvious adverse reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al found that surgery after steroid treatment has a faster curative effect and a lower recurrence rate than steroid treatment alone ( 22 ). Zhang et al found that TCM YangHe decoction combined with surgical treatment had a higher cure rate and a lower recurrence rate than surgical treatment alone ( 23 ). Zuo et al also believed that the treatment of GLM with integrated traditional Chinese and Western medicine could improve the aesthetics of both breasts, thus it is worthy of clinical recommendation ( 24 ).…”
Section: Discussionmentioning
confidence: 99%